PENGENDALIAN DALAM PENGOLAHAN DATA TRANSAKSI MELALUI AUTOMATED TELLER MACHINE PADA PT. BANK MANDIRI (PERSERO) - Piter Nainggolan (Jurnal Akuntansi Bisnis, 2017)
Internal control plays an important role in operational activities, automated teller machine (ATM), because the direct ATM machines contact daily with cash, either acceptance, withdrawal, payment or transfer of the balance control end shall be time-limited, without the Bank working hours. Cash has the highest risk because easily redirect in circulation, so we need a reliable system of internal control systems records are computerized, so all information is transferred into the information system you can trust level of precision. Key Word : Pengendalian, Automated Teller Machine(ATM)